The Effect of Employee Involvement and Workload on Employee Performance Through Work Motivation at PT. Wijaya Karya Beton Deli Serdang Branch Office - Hagatha, Izuramana; Lumbanraja, Prihatin; Siahaan, Elisabet (Indonesian Journal Publisher, 2025)
Employee performance improvement is a top priority for PT. Wijaya Karya Beton Deli Serdang Branch Office in supporting the achievement of production and service targets. In a dynamic work environment, achieving optimal performance is the main goal of every organization. Employee engagement and workload are two factors that can affect performance, both directly and through work motivation. This study aims to identify and analyze the effect of employee engagement and workload on employee performance through work motivation as a mediating variable at PT. Wijaya Karya Beton Deli Serdang Branch Office. This study is a descriptive study with a quantitative approach. The population and sample of the study were 89 employees of PT. Wijaya Karya Beton Deli Serdang Branch Office. The data analysis method used structural equation modeling. The results showed that employee engagement, workload, and work motivation had a positive and significant effect on employee performance. Employee engagement and workload had a positive and significant effect on work motivation. Work motivation mediates the effect of employee engagement and workload on employee performance.